2011
DOI: 10.1017/s0007114511003862
|View full text |Cite
|
Sign up to set email alerts
|

Oral hydroxycitrate supplementation enhances glycogen synthesis in exercised human skeletal muscle

Abstract: Glycogen stored in skeletal muscle is the main fuel for endurance exercise. The present study examined the effects of oral hydroxycitrate (HCA) supplementation on post-meal glycogen synthesis in exercised human skeletal muscle. Eight healthy male volunteers (aged 22·0 (SE 0·3) years) completed a 60-min cycling exercise at 70-75 % _ VO 2 max and received HCA or placebo in a crossover design repeated after a 7 d washout period. They consumed 500 mg HCA or placebo with a high-carbohydrate meal (2 g carbohydrate/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 29 publications
(42 reference statements)
3
38
0
Order By: Relevance
“…Recent studies suggested that during the postexercise recovery, reducing carbohydrate utilization as a fuel effectively enhances skeletal muscle glycogen repletion. For example, oral administration of hydroxycitrate, which increases energy reliance on fat oxidation during the post-exercise phase, improved glycogen repletion in skeletal muscle (24). In contrast, accelerating carbohydrate oxidation by exposure to hot conditions impaired post-exercise glycogen resynthesis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that during the postexercise recovery, reducing carbohydrate utilization as a fuel effectively enhances skeletal muscle glycogen repletion. For example, oral administration of hydroxycitrate, which increases energy reliance on fat oxidation during the post-exercise phase, improved glycogen repletion in skeletal muscle (24). In contrast, accelerating carbohydrate oxidation by exposure to hot conditions impaired post-exercise glycogen resynthesis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported that (-)-HCA increases weight loss [19, 20], promotes energy expenditure [21-23], increases the rate of glycogen synthesis [24] and suppresses de novo fatty acid synthesis [25-27]. Recently, our laboratory found that (-)-HCA treatment promoted protein synthesis and enhanced energy expenditure in male rats [28].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, increased ability of skeletal muscle to oxidise fat and sparing of muscle glycogen stores is an important phenomenon to improve the endurance performance. In this context, oral administration of hydroxycitrate has been shown to enhance the glycogen synthesis in exercised human skeletal muscle (Cheng et al, 2012). Glycogen synthesis is regulated by a number of physiological events, including training status, exercise routines and diet (Ivy, 1991).…”
Section: Introductionmentioning
confidence: 99%